Experiências e compreensões da docência com professoras de educação infantil pública de Santa Maria/RS - Rosa, Katiane Silva da (2022)
This study is linked to the Professional Master's degree of the Federal University of Santa Maria (UFSM) in the line of research 2 - Pedagogical Management and Educational Contexts and has as main objective to investigate about the understandings about teaching with children, observing and accompanying the work a group of teachers working in Early Childhood Education of Santa Maria-RS. This research is anchored in the understanding that Public Educational Policies guide Early Childhood Education as a whole, so, in view of this, we tried to understand what determined the different educational practices, in contexts of Municipal Schools for Early Childhood Education (EMEIs) and Municipal Elementary Schools (EMEFs). Throughout the research, metaphors were used in order to represent the movements of the research. This research was developed through a qualitative approach, being considered of an applied nature and implicated, because it is tied to the Municipal Public Network of Santa Maria, the researcher's work context. Data collection was performed with five teachers working in Early Childhood Education, one EMEI and three EMEFs, from individual interviews and three meetings, in the focus group modality. For the purposes of analysis, these were applied as content analysis techniques, from the records of the speeches of these meetings. From the data collected, it was possible to perceive that school culture plays a strong influence on teaching practice and their ways of acting. From the collected data, it was possible to see that teaching in Early Childhood Education is composed of a multifactorial set, encompassing both institutional and peer cultures, added to personal motivation. However, it was noticed that professional teaching autonomy is relative, as it is linked to relationships and balances between powers and human coexistence. Instead, a dialogic group is proposed as a product, with bimonthly meetings between research participants, in order to strengthen and continue the reflective process initiated in data collection meetings, sharing experiences and knowledge in a collaborative way.